An international Real Estate Advertisement System - Advertising Real Estate world-wide with European Business Partners HB - Lamrani Abou Elassad, Yassine (My University, 2011)
There are over 324,697,205 [4] websites on the internet as of May 2011. What I’m aiming to create, conjointly with European Business Partners HB, is not just yet any other website or electronic service. Indeed, the goal is to create an international space where users from across many countries can advertise a property or search for one in the nicest and easiest way possible. By making the website international, the average customer wouldn’t have to try and look for the real estate website local to every country. Take for example the case of an American student wanting to go to France for studies. Normally he’d try Google to search for a website that advertises French apartments. The search word he types would usually be in English. However a good local website will most likely be in the country’s language, which in this case is French. And so, the student in our example would have difficulties progressing with his travel. Consequently, the project’s purpose is to provide a solution to this type of problem and many others. In this report, then, I will be discussing some of these issues related to the world of real estate advertisement, some improvements I thought of, and the results I have achieved. Some of the results that illustrate a solution to the aforementioned problem would be to add a translation tool to the website. So that even if a property’s description is written in a different language, it would require little effort to translate. Also, the general solution I am proposing is to aggregate all ads of every country inside one website. And to do that, two main steps are necessary: First: Build an attractive website that offers as many facilities and innovative features to the user as possible. Second: Market the website, and publicize it. To achieve the second step, the company and I decided to first start by marketing the website in one country at a time. First, we’d start by a general English website, which would serve as our template website. Then this latter one will be translated into Swedish, and it will be marketed in Sweden. Indeed, the approach is to market it in one country at a time, until it gains strong popularity. And for each of these countries, the website will provide geographical, language, and technical support. Overall, throughout this report, I will provide more in-depth explanation of the problem at hand, a thorough investigation of possible solutions, and finally the results achieved, with examples of the implemented website. I will also discuss at the end all future work still underway.
Keywords: Programvaruteknik; Software Engineering